Material and Casting Methodology for SCC and HPC (70 MPa) Concrete Foundation Blocks - Britez, C.; Gadea, J.; Carvalho, M.; Helene, P. (Revista ALCONPAT, 2016)
The Brookfield Century Plaza Commercial Building, located in Alphaville District, in São Paulo, Brazil, was designed to be supported by two direct foundation concrete blocks. A high strength (70 MPa), self-compacting concrete SCC was developed for these two massive foundation blocks (each one measures 28.4m x 18.6m by 4.5m, high). A numerical model by employing a FEM software was developed to predict the thermal hydration gain of different casting procedures, in order to establish the most appropriate one to meet the construction and schedule requirements without cracks. Directions to control concrete production at mixing plant and placing at construction site were established as well as supervised. Finally, internal concrete temperatures were recorded to enable a better model calibration.Keywords: High strength concrete, self-compacting concrete, concrete modeling, refrigerated concrete production.